Value Management in the Nigerian Construction Industry: Challenges and Prospects - Victoria Hassana Jiya; Emmanuel Ogunleye; Collins Onuzulike; Ebenezer Ogırıma Akande; Michael Toryila Tiza (Journal of Management Studies and Development, 2023)
This study aimed to examine the state of value management in the Nigerian construction industry and to identify the challenges and prospects associated with its implementation. The study found that there is a lack of research on value management in the Nigerian construction industry, with a focus on the challenges and barriers rather than the benefits and best practices. The study also found that value management is not widely implemented in the industry, with limited understanding of the factors impacting its implementation. Specific challenges and barriers to the implementation of value management in the Nigerian construction industry were identified, such as lack of standardization and lack of expertise. Additionally, the study found that there is a limited adoption of international standards and best practices in value management, which could improve the performance of the industry. The study also found that there is a lack of training and education programs for construction professionals in value management, which is essential for effective implementation. Finally, the study found that there is a limited use of technology and data analytics to support value management in the Nigerian construction industry. Overall, the study highlights the need for further research, training and the adoption of international standards and best practices in order to improve the implementation of value management in the Nigerian construction industry.